Modulation Of Dopaminergic System By Mitragynine And The Underlying Mechanisms Instigating Impairment Of Hippocampal Synaptic Plasticity - Salim, Mohamad Azmeer Effendy Md (2023)
Mitragynine is the primary indole alkaloid of kratom (M. speciosa) Korth and is thought to be part of kratom’s main psychoactive components. Besides contributing to the addiction, it is known to induce rewarding effects by acting as an agonist to opioid receptors and block the dopamine D2 receptor. Moreover, mitragynine causes cognitive deficit and impairs the hippocampal synaptic plasticity, but the underlying mechanisms are still unknown. In the early part of the study, the modulation of dopaminergic system by mitragynine was investigated in rats treated with mitragynine (1 and 30 mg/kg) acutely (1-day treatment) and repeatedly (4-days treatment) through electroencephalography (EEG) recording. Level of dopamine release was quantified using electrochemical biosensor and ELISA kit analysis. The expression of dopamine transporter was measured using RT-qPCR. Results indicated that administration of mitragynine at both doses triggered changes in spectral frequencies demonstrating adaptations of dopaminergic system in freely moving rats. Repeated exposure of mitragynine (1 and 30 mg/kg) evoked increase of dopamine release after 4 days of administration, where at low dose (1 mg/kg) shows irregular increase of mitragynine released. High dose (30 mg/kg) shows a stable intensification of dopamine released, not after acute exposure in real time recording through an electrochemical biosensor. The adaptations of dopaminergic systems by mitragynine are coupled with increased expression of dopamine transporter in the prefrontal cortex.